2023
DOI: 10.24084/repqj01.347
|View full text |Cite
|
Sign up to set email alerts
|

The Use of an Active Power Filter for Harmonic Elimination, and Power Quality Improvement in a Nonlinear Loaded Electrical Installation.

Abstract: Consumer electronics, domestic appliances and a large range of industrial applications, namely power electronics based, can cause high disturbances in the supplied electricity. In this paper, the power quality characteristics is addressed in terms of the related standards and in the possible measures to increase it. Going from single to three phase networks and discussing passive and active filtering solutions, the paper presents simulation and experimental results obtained with a three phase active filter pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The impedance of the "LC" branch is zero at cut-off-frequency to make the output voltage equal to zero at this frequency. The cut-off-frequency is determined by making the value of inductive reactance equal to the capacitive reactance, which results in Equation (1).…”
Section: Extraction Of Reference Current Signal Using Digital Notch F...mentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance of the "LC" branch is zero at cut-off-frequency to make the output voltage equal to zero at this frequency. The cut-off-frequency is determined by making the value of inductive reactance equal to the capacitive reactance, which results in Equation (1).…”
Section: Extraction Of Reference Current Signal Using Digital Notch F...mentioning
confidence: 99%
“…Rapid development in the power electronics domain has resulted in significant impacts in many applications, where harmonic currents are injected into the utility system by power electronic loads [1,2]. The dependence of a large amount of equipment on this affects the power quality due to the presence of harmonics in the network voltages and currents.…”
Section: Introductionmentioning
confidence: 99%
“…However, Daniel et al [16] have used hybrid active filter using reduced switch topology (B4) to ensure better cost minimization and bridge losses. Study towards enhancing power quality was witnessed in the research paper of Martins [17]. However, it was found that the most effective work studied till date is the design of active power filter proposed by Moran et al [18] The author have considered reactive power for designing the power circuit and control circuit, where the experiment were carried out on 5-kVA prototype using IGBT switches.…”
Section: Existing Techniques Of Active Power Filtermentioning
confidence: 99%